An investigation on supersonic bevelled nozzle jets - Wu, Jie (2017)
This paper reports upon a numerical and experimental study on supersonic jets exhausting from bevelled nozzles with 30° and 60° exit inclination angles. To begin with, a simple but effective method to design a shock-free convergent–divergent circular jet nozzle to produce a well-conditioned supersonic Ma = 1.5 jet based on simple circular fillets is presented. Subsequently Reynolds-Averaged Navier–Stokes simulations of circular non-bevelled and bevelled nozzle jets were performed at over-expanded, perfectly expanded and under-expanded conditions. Lastly, these supersonic jets were visualized experimentally using a modified Z-type Schlieren system. Results show that the shock cell structure within the jet potential core changes from a diamond pattern to triangular and rectangular patterns as the nozzle pressure ratio and inclination angle are varied. Furthermore, jet plumes are deflected differently when the bevelled nozzles were operated at off-design conditions, with changes to the supersonic jet potential core length. Finally, quantitative analysis of the results reveals that bevelled nozzles are able to reduce the intensity of the supersonic jet shock cell structure considerably, which is potentially useful for broadband shock-associated noise mitigation purposes.